PEMURNIAN DAN KARAKTERISASI INHIBITOR PROTEASE DARI Chromohalobacter sp. 6A3, BAKTERI YANG BERASOSIASI DENGAN SPONS Xetospongia testudinaria [Purification and Characterization of Protease Inhibitor from Chromohalobacter sp. 6A3, Bacteria-associated with S - Tati Nurhayati; Maggy T. Suhartono; Lilis Nuraida; Sri Budiarti Poerwanto (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2010)
Various sponges has been reported to produce protease inhibitor which could inhibit protease activity of pathogenic bacteria. The previous research showed that bacteria-associated with sponge could produce bioactive compound similar to their host, including protease inhibitor. The purposes of this research were to purify protease inhibitor from Chromohalobacter sp. 6A3 and to study the characteristics of the protease inhibitor. The result showed that the protein can be extracted by 30 % (v/v) acetone, purified by gel filtration (Sephadex G-75) and finally, purified by anion exchanger (Sephadex A-50). The molecular weight of the purified protease inhibitor after gel filtration was estimated as 21,31 kDa and 17,05 kDa, but anion exchanger gave protein with estimated molecular weight of 21,31 kDa The optimum temperature and pH were 30 oC and 5 respectively. The protease inhibitor could resist heating at 30 oC for 10 minutes. Incubation of the inhibitor at 30 oC, pH 5, still retained its activity until 3 hours. The purified enzyme inhibitor was also still active after incubated at pH from 5 to 6 for 1 hour. The most susceptible substrate (enzyme) for the inhibitor was protease from P. aeruginosa. The protease inhibitor was inhibited by metal ions except Na+ 1mM. Activity of the inhibitor increased twofold by SDS 5 mM. IC 50 of the protease inhibitor was 3.48 nM. The protease inhibitor inhibited the enzyme uncompetitively.